Mediating the alpine archiscape : design and publicity for New Zealand's Tongariro National Park 1928-1984 : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sociology at Massey University, Palmerston North, New Zealand - Naismith, Jacqueline June (Massey University, 2013)
This thesis explores tourism publicity representing New Zealand’s Tongariro National Park and the Chateau hotel in the twentieth century, focusing specifically on how leaflets and brochures publicising the park worked as designed agents in the process of subjectivation. The thesis investigates how the documents’ representation of social actors in tourism landscapes rhetorically configures particular kinds of subjectivities. The objective of these investigations is to build and demonstrate a theory of ‘emplacement’ as a specific kind of subjectivation in tourism representations. This emplacement theory holds that subjects and places are co-constituted, such that the subject recognises itself in relation to the archiscape (defined as the built and natural elements of the place environment). The thesis uses this theory to analyse the historical specificity of emplacement. Publicity leaflets and brochures produced between 1929 and 1984 are selected as data for the case study. Emplacement processes in the brochures are investigated using the methods of critical semiotic and discourse analysis. Analysis has shown the rhetorical significance of luxury, and therefore of class and gender, for emplacement in the park. It has also shown how this emplacement has shifted over time. Four distinct historical moments are identified. In the late 1920s the park was constructed as a national recreation ground in which the absence of luxury is expressed as a spartan frugality. In the 1930s the park was reconstructed as a luxury playground and the subject’s status is elevated through elite scarcity. With the de- luxe family leisure-field of the 1960s, the consumption of ‘de-luxed’ leisure articulated middle-class family status. Finally, as the liminal pleasure zone of the 1970s and 1980s, a ‘post-lux’ permutation focused on the hedonic individual and a fleeting engagement with place. The thesis thus demonstrates the value of theorising emplacement as a process through which the subjects and archiscapes of representations are co-constituted and change over time.
Keywords: Tongariro National Park; Tourism brochures; Tourism marketing, New Zealand; Chateau (Tongariro National Park); Tourism marketing, Tongariro National Park; Sociology of tourism